Elevation of miR-210 Expression and Mean Arterial Pressure as Early-onset Pre-eclampsia Biomarkers, while Elevation of Matrix Metalloproteinase-2 as Late-onset Pre-eclampsia Biomarker - Nelvianti Nelson; Yusrawati Yusrawati; Joserizal Serudji; Jamsari Jamsari; Arni Amir; Afriwardi Afriwardi; Erry Gumilar (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Pre-eclampsia has varying onset patterns, which are challenging to determine due to their association with diverse clinical parameters, including blood pressure regulation, vascular remodeling, and placental hypoxia. These parameters influence the expression of key biomarkers such as microRNAs, metalloproteinases, and arterial pressure indices. Therefore, understanding the associations is crucial for improving early diagnosis and management. This study was conducted to compare miR-210 expression, mean arterial pressure (MAP), and matrix metalloproteinase (MMP)-2 levels between early-onset pre-eclampsia (EOPE) and late-onset pre-eclampsia (LOPE).METHODS: Pregnant women with EOPE (20–34 weeks) and LOPE (35 weeks to term) were included in this cross-sectional comparative study, and their blood samples were collected. miR-210 expression was quantified with reverse transcription polymerase chain reaction (RT-PCR), MAP was measured using sphygmomanometer, while MMP-2 levels were measured using enzyme-linked immunosorbent assay (ELISA).RESULTS: miR-210 expression was more frequently observed in the EOPE group (87.5%) compared to the LOPE group (77.5%), with a significant difference identified between the two groups. The odds ratio for miR-210 expression in EOPE compared to LOPE was 2.03 (95% CI: 1.06–6.72). The MAP was notably higher in the EOPE group (121.15 mmHg) than in the LOPE group (116.15 mmHg), with a significant difference observed. Conversely, MMP-2 levels were significantly higher in the LOPE group (390.99 ng/mL) compared to the EOPE group (271.35 ng/mL).CONCLUSION: There are significant differences in miR-210 expression, MAP and MMP-2 between EOPE and LOPE. These findings suggest that miR-210, MAP, and MMP-2 could be useful biomarkers for distinguishing between EOPE and LOPE, potentially guiding more effective management and intervention strategies.KEYWORDS: miR-210, MAP, MMP-2, EOPE, LOPE, pre-eclampsia